Chin Augumentation In Temporoman-Dibular Ankylosis - Dr. J.K. Sinha; Dr. K.K. Mangal (Indian Journal of Plastic Surgery)
In T.M. Joint ankylosis cases post operatively, normal facial contour and profile cannot be achieved although trismus is relieved. Development of mandible and facial skeleton by puberty exaggerate this problem. Not only is there chin retrusion, wide lip separation, there are also problems related to obliquely placd protruding upper and lower incisor and canines, in need of further treatment. Chin augumentation at puberty by sialistic implant, to bring about normal chin appearance and face profile is discussed.